1988
DOI: 10.1002/1097-0142(19881115)62:10<2239::aid-cncr2820621028>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle neoplasms of the uterus other than ordinary leiomyoma: A study of 46 cases, with emphasis on diagnostic criteria and prognostic factors

Abstract: Thirty-seven cases of uterine leiomyosarcoma are presented, along with nine cases of leiomyoma variants from which they were distinguished. All patients were followed for a minimum of 10 years. In cases with nuclear pleomorphism, leiomyosarcoma was diagnosed when there were five or more mitotic figures in ten consecutive high-power (X400) fields in the most active area of the tumor, and also when there were fewer mitotic figures but extensive tumor necrosis (there was only one leiomyosarcoma without nuclear pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(57 citation statements)
references
References 19 publications
5
49
1
1
Order By: Relevance
“…In recent studies, tumor size was found to be a prognostic factor for stage I disease, and both 5 and 10-cm thresholds were proposed (9,(19)(20)(21). Moreover, in our study, the mean tumor size was statistically significantly larger in the LMS group (11.88±7.79) than in the AL and CL group (p=0.008).…”
Section: Discussionsupporting
confidence: 62%
“…In recent studies, tumor size was found to be a prognostic factor for stage I disease, and both 5 and 10-cm thresholds were proposed (9,(19)(20)(21). Moreover, in our study, the mean tumor size was statistically significantly larger in the LMS group (11.88±7.79) than in the AL and CL group (p=0.008).…”
Section: Discussionsupporting
confidence: 62%
“…En önemli prognostik faktör tanı sırasındaki tümörün yaygınlığıdır. Diğer önemli kötü prognostik faktörler ise yaş, tümör çapıve mitotik sayının çokluğudur (10)(11)(12)(13)(14). LMS'lar zaman zaman tanı güçlüğü yaratabilmektedirler.…”
Section: Discussionunclassified
“…Many studies have demonstrated a relationship between cytologic atypia and outcome for uterine smooth muscle tumors (1,(15)(16)(17). The problem, as always, is defining significant atypia in a way that is reproducible and easily communicated to others.…”
Section: Atypiamentioning
confidence: 99%
“…Leiomyosarcomas are most often hemorrhagic and soft, and many feature the celebrated fish flesh texture. The usual leiomyosarcoma more often than not is more than 5 cm in diameter (15,16). Microscopically, it is easily recognized as malignant in the vast majority of cases, and usually there is no difficulty in identifying it as a smooth muscle neoplasm.…”
Section: Leiomyosarcomamentioning
confidence: 99%
See 1 more Smart Citation